Tracing the Trajectory of Cursing God in Extreme Metal - Podoshen, Jeffrey (Théologiques, 2018)
This essay examines the trajectory and the major milestones in “cursing God” in the extreme metal scene. The goal of this work is to begin a more honest conversation about the relationships between God, Satan and extreme metal that goes beyond media sensationalism. Three categories of “cursing God” in the extreme metal scene are presented and these are intended to act as a springboard for continued discourse and discussion that grants further elaboration on the intent and philosophies of the artists.